Edukasi Pengelolaan Sampah dan Pencegahan Perilaku Merokok di RW 004 Kelurahan Leuwinanggung - Safrudin Safrudin; Nana Mulyana; Nurdahlia Nurdahlia; Annisa Rahma Dewi; Fadhlurrohman Nabil; Arya Duta Lihanda (Penerbit Goodwood, 2026)
Purpose: The objective of the study was to enhance community understanding and awareness regarding waste management and smoking prevention, as both factors have detrimental effects on health and the environment within the community. Methodology: This study used a participatory educational approach involving 33 residents of RW 004, Leuwinanggung. The intervention included interactive sessions, group counselling, waste segregation and composting demonstrations, and smoking prevention discussions. A simple quantitative pre-test and post-test design with 10 questions was applied to measure participants’ knowledge before and after the program. Data were analyzed descriptively to assess changes in average scores and community awareness levels. Results: There was a notable increase in the average knowledge score of participants from 40.8% prior to the intervention to 85.7% afterward, reflecting a gain of 44.9 percentage points. Participants showed enhanced awareness of the risks associated with smoking and the principles of 3R (Reduce, Reuse, Recycle) in terms of waste management. Conclusions: The educational program successfully improved the community’s knowledge and awareness regarding waste management and smoking prevention. Ongoing initiatives utilizing health promotion theories such as the Health Belief Model and the Cek kesehatan secara rutin, Enyahkan asap rokok, Rajin aktivitas fisik, Diet seimbang, Istirahat cukup, Kelola stres (CERDIK) strategy are recommended. Limitations: While the abstract does not directly outline limitations, it is acknowledged that the study had a limited sample size of 33 participants and employed a basic pre/post-test approach. Contributions: This study shows that targeted education can improve community knowledge and awareness of environmental health and smoking prevention, supporting health promotion and policy efforts.